This is where I like to climb. Do you want me to show you? Children’s favourite places in the kindergarten outdoor playground - Anikke Hagen; Hilde Nancy Skaug (JETEN, 2022)
Abstract The study investigates children's view on preferred play spaces and what to play in the kindergarten’s outdoor playground. Walking alongside was carried out with 128 5-to 6-years old children in kindergartens in Norway. The results indicate that children's favourite places are in, by and around fixed play equipment, often with friends, where they experience motor challenges and excitement. The children used play equipment creatively and expanded the room of action by using the play equipment in other ways than intended and in connection with role play. We also noted that children's responses are not consistent with adults' thoughts on children's favourite playgrounds.